2010
DOI: 10.1073/pnas.1013210108
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of flocculin-mediated social behavior in yeast

Abstract: In the budding yeast Saccharomyces cerevisiae, self-recognition and the thereby promoted aggregation of thousands of cells into protective flocs is mediated by a family of cell-surface adhesins, the flocculins (Flo). Based on this social behavior FLO genes fulfill the definition of "greenbeard" genes, which direct cooperation toward other carriers of the same gene. The process of flocculation plays an eminent role in the food industry for the production of beer and wine. However, the precise mode of flocculin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(205 citation statements)
references
References 28 publications
(40 reference statements)
4
199
0
2
Order By: Relevance
“…These data strongly suggest that the concomitant increase of CSH and the onset of flocculation, in ale brewing yeast cells, can now be explained by the expression of flocculins on yeast cells surface. This possibility is in agreement with the fact that N-and C-terminal regions of Flo1 protein are more hydrophobic than the rest of the protein (Watari et al 1994); N-terminal region corresponds to the domain A of Flo proteins, which is responsible by the recognition and adhesion to receptors (Kobayashi et al 1998;Veelders et al 2010). …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These data strongly suggest that the concomitant increase of CSH and the onset of flocculation, in ale brewing yeast cells, can now be explained by the expression of flocculins on yeast cells surface. This possibility is in agreement with the fact that N-and C-terminal regions of Flo1 protein are more hydrophobic than the rest of the protein (Watari et al 1994); N-terminal region corresponds to the domain A of Flo proteins, which is responsible by the recognition and adhesion to receptors (Kobayashi et al 1998;Veelders et al 2010). …”
Section: Discussionsupporting
confidence: 65%
“…The N-terminal region of Flo1 protein (domain A) contains the sugar recognition domain, which is important for flocculation definition of Flo1 and NewFlo phenotypes (Kobayashi et al 1998). A detailed analysis of the adhesion domain (domain A) of the flocculin Flo5 revealed a bipartite organization constituted by a large β-sandwich domain (which is related with the PA14 domain of the anthrax-protective antigen); this domain takes an insertion, the Flo5 subdomain, which is composed by five short β-strands, stabilized by two disulphide bridges (Rigden et al 2004;Veelders et al 2010). It was also shown that calcium is directly involved in carbohydrate binding and not indirectly in the stabilization of the rodlike B domain (Veelders et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Ca 2+ binds to flocculin proteins and is necessary for flocculin to obtain the correct structural conformation 51 . A recent crystallization and structural study of flocculins showed that Ca 2+ is directly involved in carbohydrate binding 101 . Flocculation is a reversible phenomenon, so that cell flocs can be dissociated, e.g., by adding a chelating agent that removes calcium ions or by adding mannose, which competitively displaces cell wall mannose residues from flocculin binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…According to current knowledge, the flocculation of brewing yeasts occurs due to the interaction of a specific lectin-like protein (only present on flocculent cells) with the surface carbohydrate residues of the α-mannan (receptors) of neighbouring cells (Soares 2011). It was described that Ca ions are directly involved in the binding of the flocculation lectin to the α-mannan receptors (Veelders et al 2010). Yeast flocculation is influenced by characteristics of the medium and the presence of specific FLO genes (such as FLO1, FLO5,FLO8,FLO9,and FLO10) (Soares 2011).…”
Section: Sedimentation Capacitymentioning
confidence: 99%